2002
DOI: 10.1159/000067018
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Comparison of Efficacy and Preference for Rizatriptan 10 mg versus Ergotamine/Caffeine in Migraine

Abstract: Rizatriptan is a selective 5-HT1B/1D receptor agonist with rapid oral absorption and early onset of action in the acute treatment of migraine. This randomized double- blind crossover outpatient study assessed the preference for 1 rizatriptan 10 mg tablet to 2 ergotamine 1 mg/caffeine 100 mg tablets in 439 patients treating a single migraine attack with each therapy. Of patients expressing a preference (89.1%), more than twice as many preferred rizatriptan to ergotamine/caffeine (69.9 vs. 30.1%, p ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 13 publications
1
39
0
4
Order By: Relevance
“…Amongst the triptans, oral rizatriptan has been reported to be more effective than sumatriptan, naratriptan and zolmitriptan [8]. In a cross-over study, rizatriptan was found to be superior to ergotamine and caffeine combination in relieving acute migraine attack [9]. The decision to choose a new drug is based not only on its efficacy compared to placebo but also its relative advantage over other available drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the triptans, oral rizatriptan has been reported to be more effective than sumatriptan, naratriptan and zolmitriptan [8]. In a cross-over study, rizatriptan was found to be superior to ergotamine and caffeine combination in relieving acute migraine attack [9]. The decision to choose a new drug is based not only on its efficacy compared to placebo but also its relative advantage over other available drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies were financially sponsored by Merck Frosst, the maker of rizatriptan. 3,4,[6][7][8]10,[12][13][14][15] This bias likely resulted in the preference comparison of rizatriptan to the 50 mg dose of sumatriptan, rather than the 100 mg dose, which may be more effective than the lower dose of sumatriptan in some patients. 26 Furthermore, most studies compared only two attacks -one attack for each medication -which may not be enough time to determine whether a medication is effective and well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…12 Two hours after dosing, 69.8% of patients were completely, very or somewhat satisfied with rizatriptan, compared to 38.6% with ergotamine/caffeine (p  0.001).…”
Section: Dovepressmentioning
confidence: 95%
See 1 more Smart Citation
“…Patient preference is a patient-focused, composite outcome that incorporates efficacy, onset of action, duration of efficacy, consistency, tolerability and convenience of formulation [8]. Although patient preference is a subjective measurement, it addresses the central issue of which therapy is best for an individual patient and reflects how a particular treatment option is perceived by each patient with migraine [9].…”
mentioning
confidence: 99%